(untitled) (Research, Society and Development, 2022)
This study aims to bring data on the formation and development of one of the major tourist destinations in Rio Grande do Sul, the city of Bento Gonçalves, still in the condition of Imperial Colony. Princesa Dona Isabel was the denomination of the current Municipality of Bento Gonçalves, as an official Colony, between the years 1870 and 1884. Born as an Imperial Colony, today Bento Gonçalves stands out on the national scene as the main destination for wine tourism in Brazil. Exploring the early years of this colony can shed light on tourism, since it is part of the third sector that moves the city’s economy. The exploratory research, qualitative in nature, intends to contribute about the history of the town and of tourism, since the sector has taken advantage of history and culture as tourist attractions and the formation of new itineraries. The study investigates the first lodgings and discusses the role of the sheds in the initial occupation of the Italian immigration in the region.